Young Investigator: Wahajuddin. (April 2011) - Wahajuddin,
Supervisor''s supporting comments Wahajuddin has shown strong enthusiasm with equal intensity of hard work in bioanalytical research since the day he joined as a scientist in this department. His intrinsic learning abilities made him acquire deep knowledge in the area of bioanalysis and he quickly became competent in conducting regulatory/exploratory studies in pharmacokinetics, biopharmaceutics and drug metabolism –– harnessing the strengths of bioanalysis. Due to his skills and knowledge in advanced pharmaceutical analysis tools and techniques, he has also been given the responsibility to work as course coordinator for MS (Pharm.) Pharmaceutics at the newly established National Institute of Pharmaceutical Education and Research, which is an institute of national importance under the aegis of the Ministry of Chemicals and Fertilizers, Government of India. Through our Young Knowledge Promotion Initiative and Young Leadership Promotion Initiative, Wahajuddin was given the responsibility of being the corresponding author and first co-author in the majority of papers that have been published by our group, since he was instrumental in generating ideas, planning and executing the studies, compiling and analyzing the data and in writing and communicating the manuscripts. This enabled him to publish very good work in journals such as the Journal of Chromatography B, the Journal of Separation Science, Food & Chemical Toxicology, the Journal of Nutritional Biochemistry and Menopause within a very short period. Many other manuscripts are at various stages of communication and publication. His contribution also resulted in filing a patent application from the Central Drug Research Institute in 2007 (patent No.: #0081NF2007). He has also presented his work at many international conferences, symposia and seminars. He recently presented his work at the International Pharmaceutical Federation Pharmaceutical Science World Congress 2010 in association with American Association of Pharmaceutical Scientists Annual Exposition 2010 held on 14––18 November 2010 in New Orleans, USA. I am sure that he will achieve even greater feats in times to come and strongly recommend his candidature for Bioanalysis : Young Investigator 2011. Nominated by: Girish Kumar Jain, Deputy Director & Head, Division of Pharmacokinetics & Metabolism, Central Drug Research Institute, CSIR, Lucknow, India.gk_jain@cdri.res.in